The Dimensions of Parent-School Partnership - Réka Tóth; Dániel Bodnár (Debrecen University Press, 2023)
Bibliography of the reviewed special issue: Pusztai, G., & Engler, Á. (Eds.) (2020). Value-Creating Pedagogy in School and Family. Kapocs, Special Issue. Maria Kopp Institute for Demography and Families (KINCS).